RISK MANAGEMENT IN PROJECT BUSINESS –A CASE STUDY ON THE ACQUISITION OFCONSTRUCTION PROJECTS AT BILFINGER BERGER CIVIL - Schwandt, Michael (European Scientific Journal, ESJ, 2014)
This paper deals with risk management in project business. In particular, it examines the specific risks during the acquisition of construction projects. First of all the characteristics of the construction industry and the risks occurring during bid preparation and negotiation of construction projects are described. Then a case study explores which strategies the subject company pursues to manage these risks. In focus of the case study is the company Bilfinger Berger Civil, a large, international construction company, which is an active player in the project business and has already carried out a variety of construction projects successfully. The author deals with various aspects of practical risk management: optimization of the project portfolio, risk analysis and determination of the offer price with the help of a simulation model and the work of the company´s Project Controlling Department that monitors the high-risk projects. The risk management of Bilfinger Berger Civil is finally assessed in form of a summary. The reader gains information about theories on risk management and numerous impressions on their practical application in a real construction company.